Clear Low-wind Nocturnal Boundary Layers Over Topography - L. Mahrt (Boundary-Layer Meteorology, 2025)

Surface Fluxes and Flow Structure for Stably Stratified Near-Calm Conditions - L. Mahrt (Boundary-Layer Meteorology, 2024)

Heat Transport by Turbulence and Submeso Structures in the Stable Boundary Layer - L. Mahrt (Boundary-Layer Meteorology, 2024)

Types of Vertical Structure of the Nocturnal Boundary Layer - L. Mahrt; O. Acevedo (Boundary-Layer Meteorology, 2023)
The vertical structure of the observed stable boundary layer often deviates substantially from textbook profiles. Even over flat homogeneous surfaces, the turbulence may not be completely related to the surface conditions and instead generated by elevated sources of turbulence such as low-level jets and transient modes. In stable conditions, even modest surface heterogeneity can alter the vertical structure of the stable boundary layer. With clear skies and low wind speeds, cold-air drainage is sometimes generated by very weak slopes and induces a variety of different vertical structures. Our study examines the vertical structure of the boundary layer at three contrasting tower sites. We emphasize low wind speeds with strong stratification. At a given site, the vertical structure may be sensitive to the surface wind direction. Classification of vertical structures is posed primarily in terms of the profile of the heat flux. The nocturnal boundary layer assumes a variety of vertical structures, which can often be roughly viewed as layering of the heat-flux divergence (convergence). The correlation coefficient between the temperature and vertical velocity fluctuations provides valuable additional information for classification of the vertical structure.

Horizontal Variations of Nocturnal Temperature and Turbulence Over Microtopography - L. Mahrt (Boundary-Layer Meteorology, 2022)
Nocturnal spatial variation of temperature, wind, and turbulence over microtopography is generally poorly understood. Low amplitude microtopography covers much of the Earth’s surface and, with very stable conditions, can produce significant spatial variations of temperature and turbulence. We examine such variations over gentle terrain that include two shallow gullies that feed into a small valley. The gullies are covered by a sub-network of seven flux stations that is embedded within a larger network that covers the valley. The measurements indicate that gullies of only 2–5-m depth and 100-m width can often lead to spatial variations of temperature of several kelvin or more. Such variations depend on ambient wind speed and direction and the near-surface stratification. We investigate the surprising importance of microscale lee turbulence occurring over the gentle microtopography with slopes of only 5%. Near-surface stratification unexpectedly tends to increase with surface elevation on the slopes. We examine the potential causes of this puzzling behaviour of the near-surface stratification.

Small-Scale Spatial Variation of the Nocturnal Wind Field - L. Mahrt; D. Belušić; O. Acevedo (Boundary-Layer Meteorology, 2021)

Non-stationary Boundary Layers - L. Mahrt; Elie Bou-Zeid (Boundary-Layer Meteorology, 2020)

Sea-Surface Stress Driven by Small-Scale Non-stationary Winds - L. Mahrt; Erik Nilsson; Anna Rutgersson; Heidi Pettersson (Boundary-Layer Meteorology, 2020)

Small-Scale Variability in the Nocturnal Boundary Layer - L. Mahrt; Lena Pfister; Christoph K. Thomas (Boundary-Layer Meteorology, 2020)
Nocturnal variations of temperature and wind are examined at three contrasting sites. After the early evening period of rapid cooling, the magnitude of the variations of temperature on a time scale of 10 min to an hour often become larger than the corresponding temperature change due to the nocturnal trend. These shorter-term temperature variations are forced by wave-like motions and more complex modes. Observations from a network of stations across a shallow valley at one of the sites are analyzed in more detail. Typically, decreasing wind speed corresponds to less mixing and lower temperature at the surface followed by increasing wind speed, increased mixing, and higher temperatures. The flow may continue to switch back and forth between these two states for much of the night. These non-stationary motions interact with motions induced by the gentle local topography, leading to intermittent local drainage flows, transient cold pools, and both propagating and semi-stationary microfronts.

Near-Surface Vertical Flux Divergence in the Stable Boundary Layer - L. Mahrt; Christoph K. Thomas; Andrey A. Grachev; P. Ola G. Persson (Boundary-Layer Meteorology, 2018)

Directional Shear in the Nocturnal Atmospheric Surface Layer - L. Mahrt (Boundary-Layer Meteorology, 2017)

Heat Flux in the Strong-Wind Nocturnal Boundary Layer - L. Mahrt (Boundary-Layer Meteorology, 2017)

Stably Stratified Flow in a Shallow Valley - L. Mahrt (Boundary-Layer Meteorology, 2017)

Edgar “Ed” L Andreas 1946–2015 - L. Mahrt (Boundary-Layer Meteorology, 2016)

Surface Stress with Non-stationary Weak Winds and Stable Stratification - L. Mahrt; Christoph K. Thomas (Boundary-Layer Meteorology, 2016)

Dependence of Turbulent Velocities on Wind Speed and Stratification - L. Mahrt; Jielun Sun; David Stauffer (Boundary-Layer Meteorology, 2015)

Heterogeneous Nocturnal Cooling in a Large Basin Under Very Stable Conditions - D. Martínez; M. A. Jiménez; J. Cuxart; L. Mahrt (Boundary-Layer Meteorology, 2010)

Horizontal diffusion by submeso motions in the stable boundary layer - L. Mahrt; R. Mills (Environmental Fluid Mechanics, 2009)

The Influence of Transient Flow Distortion on Turbulence in Stable Weak-Wind Conditions - L. Mahrt (Boundary-Layer Meteorology, 2008)

The influence of nonstationarity on the turbulent flux–gradient relationship for stable stratification - L. Mahrt (Boundary-Layer Meteorology, 2007)

Turbulent carbon exchange in very stable conditions - Otávio C. Acevedo; Osvaldo L. L. Moraes; David R. Fitzjarrald; Ricardo K. Sakai; Larry Mahrt (Boundary-Layer Meteorology, 2007)

Observations of the cross-wind velocity variance in the stable boundary layer - Dean Vickers; L. Mahrt (Environmental Fluid Mechanics, 2007)

Extremely Weak Mixing in Stable Conditions - L. Mahrt; Dean Vickers (Boundary-Layer Meteorology, 2006)

A Solution for Flux Contamination by Mesoscale Motions With Very Weak Turbulence - Dean Vickers; L. Mahrt (Boundary-Layer Meteorology, 2006)

Boundary-Layer Adjustment Over Small-Scale Changes of Surface Heat Flux - L. Mahrt; Dean Vickers (Boundary-Layer Meteorology, 2005)

A study of intermittent turbulence with cases-99 tower measurments - Nakamura Reina; L. Mahrt (Boundary-Layer Meteorology, 2005)

Bulk Formulation of the Surface Heat Flux - L. Mahrt; Dean Vickers (Boundary-Layer Meteorology, 2004)

Conditional Analysis of an Internal Boundary Layer - Cheryl Klipp; L. Mahrt (Boundary-Layer Meteorology, 2003)

Nocturnal Low-Level Jet Characteristics Over Kansas During Cases-99 - R.M. Banta; R. K. Newsom; J. K. Lundquist; Y. L. Pichugina; R. L. Coulter; L. Mahrt (Boundary-Layer Meteorology, 2002)

Contrasting vertical structures of nocturnal boundary layers - L. Mahrt; Dean Vickers (Boundary-Layer Meteorology, 2002)

Shallow Drainage Flows - L. Mahrt; Dean Vickers; Reina Nakamura; M. R. Soler; Jielun Sun; Sean Burns; D.H. Lenschow (Boundary-Layer Meteorology, 2001)

Vertical Structure Of Turbulence In Offshore Flow During Rasex - L. Mahrt; Dean Vickers; Jim Edson; James M. Wilczak; Jeff Hare; Jørgen Højstrup (Boundary-Layer Meteorology, 2001)

Determination Of The Surface Drag Coefficient - L. Mahrt; Dean Vickers; Jielun Sun; Niels Otto Jensen; Hans Jørgensen; Eric Pardyjak; Harindra Fernando (Boundary-Layer Meteorology, 2001)

Surface Heterogeneity and Vertical Structure of the Boundary Layer - L. Mahrt (Boundary-Layer Meteorology, 2000)

Stratified Atmospheric Boundary Layers - L. Mahrt (Boundary-Layer Meteorology, 1999)

Nocturnal Boundary-Layer Regimes - L. Mahrt (Boundary-Layer Meteorology, 1998)

Heat Flux in the Coastal Zone - L. Mahrt; Dean Vickers; Jim Edson; Jielun Sun; Jørgen Højstrup; Jeffrey Hare; James M. Wilczak (Boundary-Layer Meteorology, 1998)

Fetch Limited Drag Coefficients - Dean Vickers; L. Mahrt (Boundary-Layer Meteorology, 1997)

Multiresolution Flux Decomposition - J. F. Howell; L. Mahrt (Boundary-Layer Meteorology, 1997)